Cultural care behaviors of multidisciplinary health workers in preventing neutropenic fever in children with leukemia after chemotherapy: an Ethnonursing study - Naviati, Elsa; Afiyanti, Yati; Allenidekania, Allenidekania; Novieastari, Enie (Universitas Airlangga, 2024)
Introduction: Neutropenic fever is commonly found in children with leukemia after chemotherapy. Fever occurs when children's immunity decreases after chemotherapy, and they are prone to infection. This study aims to describe the cultural care behaviors of multidisciplinary health workers in preventing neutropenic fever among hospitalized children with leukemia after chemotherapy. Methods: An ethnonursing study was conducted at a cancer referral hospital in Central Java, Indonesia. Data were collected through observation in two Pediatric ward and chemotherapy unit for three months and FGDs and in-depth interviews with health workers who provided care services to leukemia patients post-chemotherapy. Data were collected from 14 informants: six nurses, four doctors, two clinical pharmacists, and two nutritionists. This study employed four phases of Leininger analysis for qualitative data to develop its thematic structures. Results: The analysis of the entire data has revealed five themes: (1) performing antiseptic and aseptic techniques consistently, (2) nurse and dietician collaboration in handling eating difficulties post-chemotherapy, (3) collaborative interactions interdisciplinary in handling medication, (4) patient placement in an isolation room adjusted to patients' conditions, and (5) nurse's challenge to educate patients and their families. Conclusions: Health workers from multiple disciplines play essential roles in preventing neutropenic fever by involving patients, parents, and other family members. It is necessary for the nurses to collaborate with other healthcare professionals and educate patients, and families to participate in the care interventions for these patients in minimizing the occurrence of infection among leukemia patients.